The Effect of Health Facilities, Psychosocial Support and Service Quality on the Level of Refugee Satisfaction in the Makassar Immigration Detention Center - Nasrul H; St. Rukaiyah; Nurmadhani Fitri Suyuthi (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to analyze the influence of health facilities, psychosocial support, and service quality on refugee satisfaction at the Immigration Detention Center (Rudenim) in Makassar. The background of the study is rooted in the importance of providing dignified and human services for refugees living under constrained and stressful conditions. A quantitative approach was employed, with data collected through questionnaires distributed to 98 active residents of the detention center. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that all three independent variables have a positive and significant influence on refugee satisfaction. Health facilities showed a significant influence with a regression coefficient of 0.155 and a significance level of 0.043. Psychosocial support also had a significant effect, with a coefficient of 0.138 and a significance level of 0.022. Service quality emerged as the most dominant factor, with a coefficient of 0.443 and a significance level of 0.000. These findings suggest that improvements in healthcare services, emotional support, and overall service quality can substantially enhance the satisfaction levels of refugees. The study recommends improvements in indicators with lower scores, such as trust in healthcare services, recognition of refugees' cultural identity, and assurance in service delivery by officers. Implementing more empathetic, communicative, and responsive service strategies is key to fostering satisfaction and well-being among refugees during their stay at the detention center.